2020
DOI: 10.1590/1806-9282.66.7.1002
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinemia impact on newborn hearing: a literature review

Abstract: SUMMARY The increase in bilirubin levels in newborns can cause toxic effects on the auditory system, which can lead to hearing loss. This review aimed to verify the impact of hyperbilirubinemia in the hearing of newborns, relating audiological findings to serum levels of bilirubin. A literature review was conducted during October 2017, using the terms “hyperbilirubinemia”, “jaundice”, “infant”, “newborn” and “hearing loss”, on databases CAPES journals, MEDLINE and BIREME (SciELO, BBO). 827 studies were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…However, one study reported no statistically significant difference between UB and TSB as predictors of hearing loss. 24 In a systematic review, Teixeira et al 25 reported a statistically significant correlation between audiological (ABR) changes and bilirubin levels, although TSB, UCB, or CB was used in the studies reviewed. According to that review, where no such correlation can be found, the reasons were differences in the bilirubin levels defined as critical to the start of treatment as well as the type of bilirubin used in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study reported no statistically significant difference between UB and TSB as predictors of hearing loss. 24 In a systematic review, Teixeira et al 25 reported a statistically significant correlation between audiological (ABR) changes and bilirubin levels, although TSB, UCB, or CB was used in the studies reviewed. According to that review, where no such correlation can be found, the reasons were differences in the bilirubin levels defined as critical to the start of treatment as well as the type of bilirubin used in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of hyperbilirubinemia includes an auditory pathway problem with normal peripheral function of the ear such as non-affected hair cells ( Belal, 1975 ; Shaia, Shapiro, & Spencer, 2005 ). Studies have showed increase in ABR (Auditory Brainstem Response) latencies and interpeak intervals in hyperbilirubinemia animal models ( Shapiro & Hecox, 1989 ; Teixeira, Borges, Riesgo, & Sleifer, 2020 ). This phenomenon can be explained by the degenerative appearance of the spiral ganglion, where the neurons demonstrate decreased size and a lack of myelinated axons ( Shaia et al, 2005 ).…”
Section: Environmental Causes Of Congenital Hearing Lossmentioning
confidence: 99%
“…The auditory system is sensitive to the neurotoxicity of bilirubin. In fact, it is believed that the cochlear nuclei of the brainstem are one of the first structures impacted by a high total bilirubin level, followed by the auditory nerve [ 7 ]. This harm may happen in a lack of other classic bilirubin encephalopathy signs and is recognized as auditory neuropathy spectrum disorder (ANSD), which is often characterized by impaired auditory neural function (altered or absent auditory brainstem response audiometry (ABR) waveforms) in the existence of normal cochlear microphonics and/or cochlear otoacoustic emission [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These auditory implications might vary from slight speech and hearing processing impairments to total deafness, which is perceived by ABR audiometry; hence, an abnormal ABR result signifies the presence of acute bilirubin encephalopathy (ABE) and is considered the most common and the earliest manifestation of ABE [ 7 ].…”
Section: Introductionmentioning
confidence: 99%